integration(cosx+sinx)^2dx
Answers
Answered by
2
Step-by-step explanation:
Explanation:
∫
(
sin
(
x
)
+
cos
(
x
)
)
2
d
x
=
∫
sin
2
(
x
)
+
cos
2
(
x
)
+
2
sin
(
x
)
cos
(
x
)
d
x
{Expanding}
=
∫
1
+
2
sin
(
x
)
cos
(
x
)
d
x
{Since
sin
2
(
x
)
+
cos
2
(
x
)
=
1
}
=
∫
1
d
x
+
2
∫
sin
(
x
)
cos
(
x
)
d
x
{Linearity of integration}
=
x
+
C
+
2
∫
sin
(
x
)
cos
(
x
)
d
x
Now, substitue
u
=
sin
(
x
)
, or
d
x
=
d
u
cos
(
x
)
=
x
+
C
+
2
∫
u
cos
(
x
)
cos
(
x
)
d
u
=
x
+
C
+
2
∫
u
d
u
=
x
+
C
+
2
u
2
2
=
x
+
C
+
u
2
=
x
+
sin
2
(
x
)
+
C
Answered by
2
have a nice day.................
Attachments:
![](https://hi-static.z-dn.net/files/d9b/d54941649b433b784fa29b43fcc77eb4.jpg)
Similar questions
English,
6 months ago
Social Sciences,
6 months ago
History,
1 year ago
History,
1 year ago
Math,
1 year ago